2001
DOI: 10.1002/1521-3927(200102)22:2<109::aid-marc109>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Polycondensation of Terephthalic Acid and 3,3′-Dimethyl Bisphenol A with TsCl/DMF/Py in the Presence of Salts

Abstract: When activated with TsCl/dimethylformamide/pyridine in the presence of lithium, ammonium, or phosphonium salts, activated terephthalic acid of difficult solubility in pyridine became soluble. Depending on the kind and amount of the salt, terephthalic acid reacted smoothly with 3,3′‐dimethyl bisphenol A to yield the corresponding polymer having high molecular weight. However, this reaction could not be successfully applied to the preparation of polyesters from other dicarboxylic acids of difficult solubility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…Separately prepared, II IPA and II TPA were insoluble at room temperature in Py, but a mixture of II IPA and II TPA , obtained by the acti- vation of a mixture of 70 mol % IPA and 30 mol % TPA, was soluble even at room temperature. In addition, II TPA was insoluble at the boiling point of Py but became readily soluble at 100°C by the activation of TPA in the presence of LiCl or ammonium and phosphonium salts 10 and when heated in the presence of these salts.…”
Section: Resultsmentioning
confidence: 99%
“…Separately prepared, II IPA and II TPA were insoluble at room temperature in Py, but a mixture of II IPA and II TPA , obtained by the acti- vation of a mixture of 70 mol % IPA and 30 mol % TPA, was soluble even at room temperature. In addition, II TPA was insoluble at the boiling point of Py but became readily soluble at 100°C by the activation of TPA in the presence of LiCl or ammonium and phosphonium salts 10 and when heated in the presence of these salts.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous types of preparation procedures have been reported7–27 for aromatic polyester besides polycondensation with eliminating acetic acid. Among them, direct polycondensation15–27 is very attractive to control the morphology of aromatic polyesters because the condensation reagent must influence significantly the morphology. The direct copolycondensation of p ‐hydroxybenzoic acid (HBA) and other monomers has been reported 15–24.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, direct polycondensation15–27 is very attractive to control the morphology of aromatic polyesters because the condensation reagent must influence significantly the morphology. The direct copolycondensation of p ‐hydroxybenzoic acid (HBA) and other monomers has been reported 15–24. However, the direct homopolymerization of HBA has not been examined in detail because of the precipitation during polymerization, and research on the morphology of POB has not been conducted to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…An equivalent of LiCl with respect to the carboxyl groups of the diacids was used because it was most effective. 6 LiCl participated during several stages of the reaction (Scheme 1). (TPA) m and (TPA) n denote hydrogen-bonded aggregates of unactivated terephthalic acid, m and n being the degrees of aggregation (m Ͼ n).…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5] However, the reaction with dicarboxylic acids, such as terephthalic acid (TPA), does not proceed smoothly and produces only low-molecular-weight polyesters because the dicarboxylic acids activated by TsCl/DMF/Py do not dissolve in the reaction medium (Py), even at high temperatures. Recently, we have reported that activated TPA of difficult solubility in Py becomes soluble when the activation is carried out in the presence of salts, 6 such as lithium chloride (LiCl) or phosphonium and ammonium salts, or other dicarboxylic acids, 7,8 and that the reaction yields satisfactory results.…”
Section: Introductionmentioning
confidence: 99%